2y2-3y=0

Factor y out of 2y2.

y(2y)-3y=0

Factor y out of -3y.

y(2y)+y⋅-3=0

Factor y out of y(2y)+y⋅-3.

y(2y-3)=0

y(2y-3)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

y=0

2y-3=0

Set the first factor equal to 0.

y=0

Set the next factor equal to 0.

2y-3=0

Add 3 to both sides of the equation.

2y=3

Divide each term by 2 and simplify.

Divide each term in 2y=3 by 2.

2y2=32

Cancel the common factor of 2.

Cancel the common factor.

2y2=32

Divide y by 1.

y=32

y=32

y=32

y=32

The final solution is all the values that make y(2y-3)=0 true.

y=0,32

The result can be shown in multiple forms.

Exact Form:

y=0,32

Decimal Form:

y=0,1.5

Mixed Number Form:

y=0,112

Solve for y 2y^2-3y=0